Thinking Across Capability Model for Accessibility of People's Business Credit (KUR) Capital for Micro Business Actors - Suryawati, Dina; Hidayah, Nurussyamsil; Rohman, Hermanto (Indonesian Association for Public Administration, 2024)
This research examines the central government's facilitation to foster the resilience of MSME actors through capital financing, namely the People's Business Credit (KUR) program. The implementation of capital assistance through KUR remains problematic, especially the accessibility. The main objective is to analyse the problem situations and dynamics of micro-business capital and provide recommendations in the form of an adaptive and innovative policy construction model to the government. This research utilises the Soft Systems Methodology (SSM) perspective, which can transform a complex, unstructured problem into a more structured problem situation and build a conceptual model that fits the context of the existing problem. The results indicate that the primary problem is the dominance of the KUR program's policy control by the central government, which complicates capital accessibility, especially for micro businesses, and limits the authority of local governments. The proposed conceptual model focuses on thinking across capabilities, which allows the adoption of thoughts, opinions, and ideas outside the inherent cultural framework to create innovative and adaptive policy outcomes. The two main dimensions of the model application are delegated task and authority, which is the power to delegate and provide insight or the ability to produce innovative and adaptive thinking. This resulted in two recommendations for the mandate mechanism to local governments, namely (1) authorising local governments to make recommendations for business status based on mapping to provide a guarantee for micro-businesses (2) the authority of local governments to work with banks to facilitate the distribution and bureaucratic management of KUR financing to micro businesses.